(untitled) (REMUNOM, 2026)
Avocado (Persea) is a fruit widely cultivated and consumed in Brazil, however there is still scarce information on the nutritional profile of varieties grown in Brazil. The objective of this study was to quantify and compare the protein, total lipid, moisture and ash contents of five avocado varieties. The centesimal analysis was carried out on the varieties Breda, Fortuna, Geada, Margarida and Quintal. The data were statistically analyzed through the difference and comparisons between means. The results indicated that the protein content of the Margarida variety was higher than those found in the other avocados. As for lipids, the Geada avocado presented a lower amount compared to the other varieties. Moisture was observed in smaller quantities in the Fortuna avocado, followed by the Breda, Margarida, Quintal and Geada varieties. The ash values were lower in the Geada, Margarida and Quintal avocados and higher in the Breda variety. Finally, the data presented show the inexistence of a single pattern of centesimal composition of avocados, indicating the existence of relevant variations in the nutritional profile of the five varieties studied, expanding the possibilities of their food use